STUDENT CAREER MATURITY: THE ROLE OF SELF-EFFICACY AND INTERNAL LOCUS OF CONTROL - Azhari, Muhammad Badrani; Wibowo, Agus; Febriantina, Susan (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
Vocational High School (SMK) as a bridge between prospective graduates and jobs, through education makes individuals more competent in working than other education. However, SMK graduates are the largest contributor to the percentage of unemployment based on education, namely 10.38% in 2022. This study aims to determine whether or not there is an influence between Self-Efficacy and Internal Locus of Control on the Career Maturity of Students at Public Vocational High Schools 40 Jakarta. The method used in this study is quantitative using Structural Equation Modeling (SEM) with SmartPLS version 4. The probability sampling technique, namely simple random sampling and the Slovin formula, is used to determine the sample with a 5% error rate, namely 138 students. Data collection was obtained through a Likert scale questionnaire. Based on data calculations, the results of this study indicate that there is a significant influence between Self-Efficacy and Internal Locus of Control on Students’ Career Maturity both simultaneously and partially. It is hoped that schools can increase activities related to the world of careers and individuals can further improve their preparation for their careers.